Analisis Generasi F2 dan Seleksi Pertama dari Persilangan Kedelai antara Kultivar Slamet dan Wase - Suharsono, ,; Jusuf, Muhammad (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2009)
The research had an objective to analyse the population of F2 and first selection (S1) generations of the cross between soybean cultivar Slamet and Wase. The ultimate goal of this research is to obtain the elite cultivars of soybean having high yield, big seeds, and tolerant to acid and aluminum stresses. The genetic variance and heritability in the broad sense of all characters observed of F2 population were very high. The seed productivity of F2 population was higher than that of Slamet and Wase cultivars. The size of seeds of F2 population was bigger than that of Slamet and comparable to that of Wase. The heritability in the broad sense of all characters of F2 population was very high because the maximum segregation occurs in F2 and the two parents had a very different genetic back ground. By using 7.5% selection intensity based on productivity, we got selected F2 population having productivity two times than that of Slamet. Seeds of this selected F2 population were bigger than that of F2 population and cultivar Slamet. The S1 population had seed productivity higher than Slamet and Wase cultivars. The heritability in the broad sense of all characters of S1 population was smaller than that of F2 population caused by the selection. The selection by 4.8% intensity resulted the selected S1 population having productivity three times than that of cultivar Slamet and big seeds. The selected S1 population had a phenotype variance of productivity smaller than S1 population. Therefore, the selected S1 population is very potential to be developed as elite soybean cultivars.   Key words: soybean, genetic variance, heritability, selection, F2 population